Promoting constructive agriculture and food investment in ASEAN - Azizah Nazzala Fauzi; Nisrina Nuraini Nafisah (Center for Indonesian Policy Studies (CIPS), 2021)
Food security is an urgent issue in Southeast Asia. Its population continues to grow, high rates of malnutrition, declining agricultural productivity, and the Covid-19 pandemic, worsening the situation of food availability and affordability, especially for vulnerable communities. The ASEAN Integrated Food Security framework and Strategic Plan of Action prepared by ASEAN have not been able to overcome the challenges of attracting constructive investment. This policy paper provides three practical policy recommendations to improve ASEAN's food security strategy.
Keywords: 330; Ernährungssicherung; Auslandsinvestition; Landwirtschaft; Ernährungsindustrie; Agroindustrie; ASEAN-Staaten